1969
DOI: 10.1002/oms.1210020202
|View full text |Cite
|
Sign up to set email alerts
|

Structure and fragmentation mechanisms of organic ions in the mass spectrometer

Abstract: THIS paper attempts (i) to review critically some (but not all) of the techniques which have come to be used by organic chemists during the past few years to infer positive ion structures and mechanisms for the production of fragment ions in the mass spectrometer, and (ii) to consider qualitatively some of the factors which determine the nature of mass spectra. The review is not intended by any means to be exhaustive and reference will therefore not be made to much of the earlier fundamentally important work. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1969
1969
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(21 citation statements)
references
References 86 publications
0
21
0
Order By: Relevance
“…Since it is observed here, higher activation energies are suggested to be associated with radical losses rather than with the competitive elimination reactions, the lower frequency factors for elimination reactions counterbalancing the energetic terms and leading to comparable fragmentation rates. 22 This points to the iimited validity of the even electron ion + even electron ion nile.' Additional examples of competitive radical and neutral losses on collision induced dissociation of protonated species are a~ailable.~,*~ From these results it is concluded that small proto-nated ions follow characteristic fragmentation patterns just as do odd electron ions.…”
Section: Discussionmentioning
confidence: 98%
“…Since it is observed here, higher activation energies are suggested to be associated with radical losses rather than with the competitive elimination reactions, the lower frequency factors for elimination reactions counterbalancing the energetic terms and leading to comparable fragmentation rates. 22 This points to the iimited validity of the even electron ion + even electron ion nile.' Additional examples of competitive radical and neutral losses on collision induced dissociation of protonated species are a~ailable.~,*~ From these results it is concluded that small proto-nated ions follow characteristic fragmentation patterns just as do odd electron ions.…”
Section: Discussionmentioning
confidence: 98%
“…The most notable phenomenon in our study is that the Cl-KIEs of DCM changed from large normal Cl-KIEs to extremely large inverse Cl-KIEs as the CEs varied from 0 to 60 eV, which has never been reported previously and is challenging to explain. To interpret this phenomenon, we refer to the theory in terms of competitive dechlorination reactions in EI-MS [34,35]. We take the reactions of CH2 35 Cl 37 Cl •+ →CH2 35 Cl + (H) and CH2 35 Cl 37 Cl •+ →CH2 37 Cl + (L) of DCM for example, which can be regarded as two isotope-competitive reactions during CID in MS/MS.…”
Section: Isotope-competitive Dechlorination Reactionsmentioning
confidence: 99%
“…For example, MS/MS experiments on "chiral" complexes that measure the specific dissociation energies with the "kinetic method" [88] was previously discussed by Djerassi and coworkers [89]. In these communications from the 1960s, a thorough understanding of electron ionization mass spectra allowed one to resolve structural and stereochemical problems for steroidal molecules [90]. The relative lack of 3D structural information from MS spectra is compensated when highly automated lC-uV-MS/MS-NMR platforms are utilized, as has been shown in several examples [91][92][93][94].…”
Section: The Role Of Ms In the Elucidation Of Chemical Structuresmentioning
confidence: 99%